2006
DOI: 10.1002/jrs.1653
|View full text |Cite
|
Sign up to set email alerts
|

Food additives characterization by infrared, Raman, and surface‐enhanced Raman spectroscopies

Abstract: Fourier-transform infrared (FT-IR), Raman (RS),respectively. The analysis of the SERS spectra shows that HMB interacts with the silver surface mainly through the -COO − , hydroxyl, and -CH 2 -groups, whereas L-carnitine binds to the surface via -COO − and -N + (CH 3 ) 3 which is rarely enhanced at pH = 8.3. On the other hand, it seems that creatine binds weakly to the silver surface mainly by -NH 2 , and C O from the -COO − group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 29 publications
(31 reference statements)
1
28
0
Order By: Relevance
“…Carnitine and acyl carnitines being chiral molecules, optical rotation (OR) and circular dichroism in the UV range (electronic circular dichroism, ECD) were measured; in the latter case, ECD has been used as a detector of enantiomeric separation, down the line of HPLC separation protocol, without the accuracy required in a dedicated ECD experiment. To the best of our knowledge, though, no one has ever measured vibrational circular dichroism (VCD); yet various forms of vibrational spectroscopy, including IR, Raman, and SERS (surface‐enhanced Raman spectroscopy) have been carried out and demonstrated to be useful . VCD has acquired increasing importance through the years in the chiroptical spectroscopies field and has permitted tackling several problems, including determination of the absolute configuration (AC), investigation of conformational properties, chiral recognition and conformation, and the role of biomolecules.…”
Section: Methodsmentioning
confidence: 99%
“…Carnitine and acyl carnitines being chiral molecules, optical rotation (OR) and circular dichroism in the UV range (electronic circular dichroism, ECD) were measured; in the latter case, ECD has been used as a detector of enantiomeric separation, down the line of HPLC separation protocol, without the accuracy required in a dedicated ECD experiment. To the best of our knowledge, though, no one has ever measured vibrational circular dichroism (VCD); yet various forms of vibrational spectroscopy, including IR, Raman, and SERS (surface‐enhanced Raman spectroscopy) have been carried out and demonstrated to be useful . VCD has acquired increasing importance through the years in the chiroptical spectroscopies field and has permitted tackling several problems, including determination of the absolute configuration (AC), investigation of conformational properties, chiral recognition and conformation, and the role of biomolecules.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of SERS spectrum of β-hydroxy-β-methylbutanoic acid, the bands at 1447, 880, 725, and 692 cm −1 due to CH 2 and CH 3 modes suggest that these moieties assist the molecule to bind to the silver surface. [80] In the SERS spectrum of 2-amino-5-nitropyridine, [81] the symmetric NO 2 stretching mode corresponds to the most intense band, which appears broad and significantly downshifted from 1344 to 1326 cm −1 suggesting binding to silver through the lone pairs of the oxygen atom. Carrasco et al [82] observed the NO 2 stretch in the SERS spectrum at ∼1500 cm −1 with medium intensity, which demonstrated the importance of the nitro group in regard to the interaction with the metal surface.…”
Section: Sers Spectrummentioning
confidence: 99%
“…In SERS, Raman scattering signals of an analyte are greatly enhanced through adsorption of the analyte onto a roughened metal (typically Au, Ag, and Cu) surface [8,9]. Many studies have indicated the great potential of applying SERS as an analytical tool in various areas; yet SERS is still in its early development stage in food science and aquaculture [10][11][12][13][14]. The main factors impeding the successful application of SERS by the food science researchers are the high cost and lack of resource to make effective surface enhanced substrates.…”
Section: Introductionmentioning
confidence: 99%